how can I reduce:
$co = ci'ab+cia'b+ciab'+ciab$
to: $co = ab + cia + cib$
I don't know how they did that on the book... This is for Adders, working with circuits.
Thank you very much
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It only takes a minute to sign up.Sign up to join this community
I am not an expert in circuits, but I have some doubt on your question. If you take $c = i = 0$ and $a = b = 1$, then $ci'ab+cia'b+ciab'+ciab = 0$ but $ab + cia + cib = 1$.